Cognitive abilities and time-sharing performance - Maslić-Seršić, Darja (Array, 1994)
Our previous study revealed that the measures of perceptual speed and numerical ability, rather than that of reasoning ability, correlated with time-sharing performance, suggesting that the speed of information processing may be a crucial factor in time-sharing performance. The present aim is to further examine the role of cognitive abilities in the time-sharing performance of perceptual-motor tasks by extending the analysis to higher levels of time-sharing practice. Our subjects (N=80) performed seven computerized reaction-time and tracking tasks, both singly and concurrently. The performance of as many as 30 trials was obtained during 10 successive days of practice. The subjects also completed a series of paper-and-pencil tests (mainly from the French, Ekstrom & Price's kit) comprising nine cognitive ability factors. The data are now being analyzed by a series of correlational analyses in which the primary cognitive factors are treated as the predictor variables and the single and dual-task performance at various stages of practice as the criterion variables. The obtained results will be presented and discussed.